The “Blackpink's” Influence on Oreo Purchases in Indonesia: A Consumptive Behavior Study : Pengaruh "Blackpink" terhadap Pembelian Oreo di Indonesia: Sebuah Studi Perilaku Konsumtif - Swastika, Karin Regita; Evelina, Tri Yulistyawati; Indrianti, Titien (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2024)
This quantitative study investigates the influence of consumptive behavior and brand ambassadorship, specifically focusing on the case of Blackpink, on purchasing decisions for Oreo products among Indonesian consumers. Utilizing a deductive research approach, data was gathered through a survey employing a questionnaire administered to 100 Oreo consumers who are Blackpink fans, selected through purposive sampling. Statistical analysis, including t-tests and F-tests, was employed to test hypotheses concerning the impact of consumptive behavior and brand ambassadorship on purchasing decisions. Results indicate that both factors significantly affect consumer purchasing decisions, both individually and collectively. The findings suggest avenues for future research to explore additional variables, such as fanatical behavior influenced by idol brand ambassadors, and to compare the effects of various brand ambassadors over time, thereby offering valuable insights for marketing strategies.